THE EFFECTIVENESS OF THE OMBUDSMAN OF THE REPUBLIC OF INDONESIA REPRESENTATIVES OF THE PROVINCE OF LAMPUNG IN COMPLETING REPORTS REGARDING THE DISTRIBUTION OF SOCIAL ASSISTANCE FOR COMMUNITIES AFFECTED BY THE COVID-19 NATIONAL DISASTER IN LAMPUNG - Lintje Anna Marpaung; Tami Rusli; Tegar Adiwijaya; Yulia Hesti (Wacana Hukum, 2021)
This research discusses the Effectiveness of the Ombudsman of the Republic of Indonesia Representatives of the Province of Lampung in Completing Reports Regarding the Distribution of Social Assistance for Communities Affected by the Covid-19 National Disaster in Lampung Province. With the formulation of the problem 1) How is the Effectiveness of the Ombudsman of the Republic of Indonesia Representatives of the Province of Lampung in Completing Reports Regarding the Distribution of Social Assistance for Communities Affected by the Covid-19 National Disaster in Lampung Province? 2) What were the inhibiting factors experienced and the efforts made by the Ombudsman of the Republic of Indonesia representatives of the province of Lampung in completing the report? The conclusions of this study are 1) Completion of reports related to the distribution of social assistance to communities affected by the Covid-19 national disaster in Lampung Province carried out by the Ombudsman of the Republic of Indonesia Representatives of the Province of Lampung is quite effective but not maximized, this is because the settlement regulatory mechanism is only based on in the Circular that has differences with the Ombudsman Regulations of the Republic of Indonesia 2) The main obstacle to the completion of public reports experienced by the Ombudsman of the Republic of Indonesia Representatives of the Province of Lampung is the issuance of the Circular of the Chairman of the Ombudsman of the Republic of Indonesia which overrides higher Regulations, and efforts made to overcome obstacles The Head of the Ombudsman Representative of the Republic of Indonesia, Lampung Province, took another policy in the form of continuing to use several requirements stipulated in the Ombudsman Regulation of the Republic of Indonesia.